2010
DOI: 10.26807/remcb.v31i1-2.39
|View full text |Cite
|
Sign up to set email alerts
|

Impacto genético en comunidades Amazónicas del Ecuador localizadas en zonas petroleras

Abstract: RESUMEN.-La exposición de agentes carcinógenos usados en la industria petrolera incrementa el desarrollo de cáncer tanto en hombres como en mujeres y niños. Se ha observado que los individuos expuestos a agentes genotóxicos presentan una inestabilidad general del genoma humano que puede ser evaluada por medio del estudio de cromosomas o de genes involucrados en daño genético a través del aná-lisis del nivel de fragmentación del ADN en individuos expuestos a los hidrocarburos. Para el estudio se escogieron 23 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…The sampling zones closest to the extraction wells showed a greater evidence of DNA damage than those that are farther away which suggests a distance-damage relationship. This relationship is also supported by the increased occurrence of type A nuclei (no damage) as the distance from the wells increases [88]. Another study was carried out with a significantly bigger sample size from the nearby zone of San Carlos and matching controls from both San Carlos and the country's capital Quito.…”
Section: Hydrocarbons Genotoxicity Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The sampling zones closest to the extraction wells showed a greater evidence of DNA damage than those that are farther away which suggests a distance-damage relationship. This relationship is also supported by the increased occurrence of type A nuclei (no damage) as the distance from the wells increases [88]. Another study was carried out with a significantly bigger sample size from the nearby zone of San Carlos and matching controls from both San Carlos and the country's capital Quito.…”
Section: Hydrocarbons Genotoxicity Studiesmentioning
confidence: 95%
“…Comet assay showed that the affected group has a high occurrence of type B nuclei fragmentation, as opposed to the prevalence of type A cells in the control groups from San Carlos and Quito. Additionally, the analysis of chromosomal aberrations showed that 20% of the exposed individuals presented chromosomal breaks and gaps while only 2% of the control individuals had such aberrations [ 88 ]. At a molecular level, we incorporated the analysis of the polymorphisms of the genes CYP1A1 (MspI and Ile/Val) and MSH2 (gIVS12-6T > C), both related to the development of cancer [ 58 , 59 , 89 , 90 ].…”
Section: Hydrocarbons Genotoxicity Studiesmentioning
confidence: 99%
“…Uma vez que o petróleo possui compostos com características carcinogênicas, como os HPAs, muitos autores encontraram uma associação entre diversos tipos de câncer (fígado, rins, pulmões, mama e próstata) e a exposição a locais que sofreram derramamentos de óleo (YANG et al, 2000;BOERS et al, 2005; Merhi, 2010;Paz-y-Miño et al, 2010;Harville et al, 2018 Impactos no sistema reprodutivo, tais como infertilidade, aumento do risco de aborto espontâneo e de má formação congênita, diminuição da qualidade e aumento das taxas de anormalidade do sêmen.…”
Section: Danos Físicosunclassified
“…O sistema reprodutivo pode ser severamente afetado, já que em locais mais expostos aos contaminantes o risco de aborto espontâneo tem índices mais altos (MERHI, 2010) e a qualidade do sêmen é pior (DE CELIS et al, 2000;MERHI, 2010;PAZ-Y-MIÑO et al, 2010).…”
Section: Psicológicosunclassified
“…The affectation of soil, water, flora and fauna, attributable to inappropriate practices of the petroleum industry was largely studied [7][8][9]. In addition, several reports on the negative effects on human health due to the exposure of humans to compounds associated with petroleum extraction manifesting as skin, digestive, respiratory, pregnancy and reproductive diseases, among others, were widely reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%